Structural insights into Acyl-coenzyme A binding domain containing 3 (ACBD3) protein hijacking by picornaviruses - Chalupska, Dominika; Różycki, Bartosz; Klima, Martin; Boura, Evzen (Protein science, 2019)
Many picornaviruses hijack the Golgi resident Acyl-coenzyme A binding domain containing 3 (ACBD3) protein in order to recruit the phosphatidylinositol 4-kinase B (PI4KB) to viral replication organelles (ROs). PI4KB, once recruited and activated by ACBD3 protein, produces the lipid phosphatidylinositol 4-phosphate (PI4P), which is a key step in the biogenesis of viral ROs. To do so, picornaviruses use their small nonstructural protein 3A that binds the Golgi dynamics domain of the ACBD3 protein. Here, we present the analysis of the highly flexible ACBD3 proteins and the viral 3A protein in solution using small-angle X-ray scattering and computer simulations. Our analysis revealed that both the ACBD3 protein and the 3A:ACBD3 protein complex have an extended and flexible conformation in solution.
Keywords: adaptorové proteiny signální transdukční; Picornaviridae; lidé; Binding Sites; vazebná místa; Acyl Coenzyme A; membránové proteiny; Humans; Membrane Proteins; Adaptor Proteins, Signal Transducing; acylkoenzym A